Studi Literatur Kombinasi Analisis Fundamental Dan Teknikal Sebagai Strategi Investasi Saham Yang Efektif - Manuel Vivien Ricardo Tampubolon; Yanda Bara Kusuma (Jurnal Akuntan Publik, 2024)
This literature study aims to introduce the main fundamental analysis and stock valuation methods that daily equity traders apply in choosing stocks for their active equity portfolios. Daily equities traders rely mostly on technical charts and other tools to identify patterns that can suggest potential activity without assessing a stock’s intrinsic value for trading decisions. Chart analysis is designed to find trades with high probability outcomes by establishing precise price targets. The goal of this technical paper is to emphasize the significance of fundamental analysis in the investment choices of daily traders. Fundamental analysis is based on the careful comparisons of a stock’s intrinsic value to the current market price. If the stock’s intrinsic value is higher than the market price, it is reasonable for a fundamental investor/trader to purchase the stock. This paper endorses the idea that using both investment techniques would result in more successful investing decisions for equities traders.